The Effect of Adding Ketapang Fruit Ash on the Physical and Mechanical Properties of Geopolymer Concrete Based on High-Calcium Fly Ash Type C with Alkali Activator - Martiana, Rina; Liza, Sofia Afsa; Wani, Candra; Hilmayati, Sri; Astuti, Alpiana Puji; 'Ardhuha, Jannatin (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
This study aims to analyze the effect of adding ketapang fruit ash on the physical and mechanical properties of geopolymer concrete based on high-calcium fly ash type C with an alkali activator. The research methods included chemical composition analysis of fly ash using X-Ray Fluorescence (XRF) and the preparation of concrete samples with varying concentrations of ketapang fruit ash (1%, 1.6%, 2.3%) and water content (3.6%, 3.0%, 2.3%), as well as curing durations (7, 14, and 28 days). The XRF analysis results revealed that fly ash from the Jeranjang Power Plant belongs to Class C, with major components being SiO₂ (34.8%), Fe₂O₃ (23.7%), CaO (23.0%), and Al₂O₃ (11.0%). Physical property tests indicated that the mass of concrete types I, II, and III remained relatively stable at 7, 14, and 28 days, although a slight decrease in mass was observed for concrete type I after curing, with a final mass of 6.8 kg. This decrease was attributed to environmental factors, composition, and rapid water evaporation. Mechanical property tests demonstrated a significant increase in compressive strength across all concrete samples as the concentration of ketapang fruit ash increased. The highest compressive strength was achieved by concrete type III with a ketapang fruit ash concentration of 2.3%, reaching 200 MPa at 7 days, 225 MPa at 14 days, and 270 MPa at 28 days. Furthermore, the addition of ketapang fruit ash improved the concrete's resistance to water penetration. These results suggest that incorporating ketapang fruit ash is an effective alternative for enhancing the quality of geopolymer concrete for structural applications.